Chicago Sociology - Chapoulie, Jean-Michel (Columbia University Press, 2020)
"Known for its pioneering studies of urban life, immigration, and criminality using the "city as laboratory," the so-called Chicago school of sociology has been a dominant presence in American social science since it emerged around the University of Chicago in the early decades of the twentieth century. Canonical figures such as Robert Park, Everett Hughes, Howard S. Becker, and Irving Goffman established foundational principles of how to conduct social research. This groundbreaking book on the development and influence of the Chicago tradition, first published in 2001, became an immediate classic in France, where Chicago sociology has exerted significant appeal. Drawing on deep archival research and interviews with members of the tradition, Jean-Michel Chapoulie interrogates evidence with a historian's eye and recognizes the profound effects that culture, society, and the economy have on individuals and institutions. His study is a fine-grained and panoramic portrait of the complex and interlocking factors that gave rise to the research interests and methodologies that characterized the Chicago tradition in the 1920s and that contributed to rises and falls in its predominance in American sociology over the following decades. Now revised and available for the first time in English, Chicago Sociology provides a unique perspective on the history of social science in the twentieth century. A foreword by William Kornblum places Chapoulie's work in context and addresses recent critical challenges to the Chicago school and its origins"--